Analysis of Potentials and Challenges of Culture-based Learning in Indonesia : A Systematic Literature Review - Dimas Febriansyah Krisna Dwiputra; Dadang Sundawa (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This study aims to identify the potential and challenges of culture-based learning in Indonesia. This study used the systematic literature review method with the PRISMA 2020 model. Data were collected from Harzing's Publish or Perish whose database comes from Scopus and Google Scholar. The data search used three keywords including